2011
DOI: 10.1038/onc.2011.419
|View full text |Cite
|
Sign up to set email alerts
|

TOPK/PBK promotes cell migration via modulation of the PI3K/PTEN/AKT pathway and is associated with poor prognosis in lung cancer

Abstract: We integrated four gene expression profile data sets, namely two different pair-matched stage I lung adenocarcinoma data sets, secondary metastatic tumors vs benign tumors and lung tumor metastasizes to the brain, and we identified one kinase, T-LAK Cell-Originated Protein Kinase (TOPK), as a putative gene that promotes metastasis. To delineate the role of TOPK in lung cancer, we showed that overexpression of TOPK, but not a catalytically inactive form of TOPK, can enhance the migration and invasion of lung fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
155
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(167 citation statements)
references
References 33 publications
10
155
2
Order By: Relevance
“…PBK/TOPK prevents cancer cell death by impairing processes in the DNA damage-induced apoptosis pathway (13)(14)(15), such as tumor suppressor p53 and p38-mitogen-activated protein kinase (p38-MAPK) activities. PBK/TOPK promotes cell migration by modulating phosphoinositide 3-kinase/phosphatase and tensin homolog/ AKT (PI3K/PTEN/AKT)-dependent signaling (8). However, to date, there has been no report on the clinical and prognostic significance of PBK/TOPK in patients with ESCC and its molecular function contributing to gastric carcinogenesis.…”
Section: Overexpression Of Pbk/topk Contributes To Tumor Development mentioning
confidence: 92%
See 2 more Smart Citations
“…PBK/TOPK prevents cancer cell death by impairing processes in the DNA damage-induced apoptosis pathway (13)(14)(15), such as tumor suppressor p53 and p38-mitogen-activated protein kinase (p38-MAPK) activities. PBK/TOPK promotes cell migration by modulating phosphoinositide 3-kinase/phosphatase and tensin homolog/ AKT (PI3K/PTEN/AKT)-dependent signaling (8). However, to date, there has been no report on the clinical and prognostic significance of PBK/TOPK in patients with ESCC and its molecular function contributing to gastric carcinogenesis.…”
Section: Overexpression Of Pbk/topk Contributes To Tumor Development mentioning
confidence: 92%
“…The PBK/TOPK gene is up-regulated in various types of cancer and tumors such as bladder cancer, brain tumor, breast cancer, liver cancer, lung cancer and sarcoma (7)(8)(9)(23)(24)(25)(26). PBK/TOPK was initially identified as a mitotic protein kinase (27), assisting the recruitment of cylcin-dependent kinase 1 (CDK1)/cyclin B to mitotic spindles, where PBK/TOPK plays a role in the formation of the spindle midzone and cytokinesis (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that loss of function or downregulation of PTEN resulted in tumor metastasis, and more aggressive growth behaviors of tumor, and/or poor prognostic phenotypes. 42,[49][50][51][52][53][54][55][56][57] In addition, miR-19 upregulation was observed in various cancers including lung cancer, and correlated with tumor metastasis and/or poor prognosis of cancer patients. [11][12][13][14][15]18 Given that miRNAs primarily function through inhibiting the translation of their mRNA targets, we propose that miR-19 might be a negative regulator for PTEN, which has been reported by other researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence supports that inactivation or downregulation of the tumor suppressor PTEN can trigger EMT of cancer cells, [60][61][62][63] which then promoted the invasion and metastasis of various cancers including lung cancer. 42,[49][50][51][52][53][54][55][56][57] It has been reported that PTEN negatively regulated the PI3K/ Akt pathway through the dephosphorylation of PI(3,4,5)P3, and ultimately participated in the regulation of cell cycle, proliferation, apoptosis, adhesion, and EMT during cancer progress. 63 In the present study, we found that PTEN silence through RNA interference mimicked miR-19-induced EMT, and promoted the migration and invasion of tumor cells, which were similar as the results caused by miR-19 overexpression.…”
Section: Discussionmentioning
confidence: 99%